2022
DOI: 10.1186/s12913-021-07455-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the implementation of an innovative IT solution to improve waiting times, communication with primary care and efficiency in Rheumatology

Abstract: Objective To describe in detail an innovative program based on telemedicine for semi-automated prioritization of referrals from Primary Care (PC) to Rheumatology, for reproducibility purposes, and to present the results of the implementation study. Methods The context and situation were carefully analyzed, paying attention to all processes in place, referral numbers, waiting times, and number of complementary tests prior to discharge from Rheumatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Implementation of e-consultation programmes may significantly reduce wait times while assuring prioritization of inflammatory diseases and improving communication between healthcare levels. 27 Another promising strategy is self-referral. Recent data have shown that an online self-referral tool can be used in specialized centres in addition to a physician-based referral strategy to improve early diagnosis and to increase awareness of axSpA, especially in people younger than 40 years old.…”
Section: Diagnosismentioning
confidence: 99%
“…Implementation of e-consultation programmes may significantly reduce wait times while assuring prioritization of inflammatory diseases and improving communication between healthcare levels. 27 Another promising strategy is self-referral. Recent data have shown that an online self-referral tool can be used in specialized centres in addition to a physician-based referral strategy to improve early diagnosis and to increase awareness of axSpA, especially in people younger than 40 years old.…”
Section: Diagnosismentioning
confidence: 99%
“…Background: EPISER study has confirmed the great burden of rheumatic diseases, which represent almost 30% of primary care medical consultations in Spain [1,2]. Electronic consultation could be an alternative response [3] as well as rheumatologist-led update programmes and joint case discussion with primary care physicians have shown to reduce the burden of care and waiting times in rheumatology units [4]. Objectives: To analyze the demand from primary care to the rheumatology service of a tertiary hospital.…”
mentioning
confidence: 99%